Assessment of Teacher Performance Regarding Teacher Professionalism in Educational Institutions - Puspita Sari; Benyamin Situmorang; Rosmala Dewi; Yasaratodo Wao; Hotmaida Sidabutar (Budapest International Research and Critics University, 2023)
This study discusses the assessment of teacher performance to test the professionalism of educators at Santa Lucia Sei Rotan Elementary School. The background of this study is the requirement of a professional teacher in all subjects at all levels of education. Especially with the regulations of the Teacher and Lecturer Constitution, as well as the certification of educators. So to be able to know the professionalism of teachers carry out teacher performance assessments which include four basic components, namely pedagogic, personality, social, and professional. This research is intended to answer the following problems: (1) How is teacher performance assessed at Santa Lucia Sei Rotan Elementary School?, (2) What efforts should be made by school principals to improve teacher professionalism at Santa Lucia Sei Rotan Elementary School?. This research is a type of field research. Therefore the objects studied in schools are able to provide information about research studies. In order for this research to run well, research methods require planning steps that are systematic and in accordance with scientific principles. In addition, intensive qualitative research was carried out, participating in recording all data and then analyzing the data obtained during the research. This study shows that: (1). Teacher performance can be known by carrying out teacher performance assessments which make an activity to foster and develop professional teachers who from teachers, by teachers, for teachers. The principal assesses the implementation of learning including pre-learning (checking class readiness and apperception), core activities (mastery of material, learning strategies, use of media/sources, assessment of learning processes and outcomes, use of language), and closing (reflection, summary and follow-up) (2) Efforts by school principals to improve teacher professionalism by providing (a) guidance to teachers in preparing lesson plans, (b) monitoring teachers in carrying out learning, (c) supervising the running of educational activity programs, (d) checking condition and integrity of school facilities as supporting student achievement, (e) evaluating through briefings and educational program meetings